Effects of bite-jumping appliances on mandibular advancement in growing rats: A radiographic study - Oksayan, Ridvan; Sokucu, Oral; Ucuncu, Neslihan (European journal of dentistry, 2014)
ABSTRACT Objective: The aim was to evaluate the effects of the use of mandibular advancement appliances on mandibular growth in growing rats. Materials and Methods: Twenty-four 8-week-old male Wistar albino rats were randomly divided into two experimental groups (12 rats each): Group I was a control group, and Group II was the mandibular advancement appliance group. A functional bite-jumping appliance was used in Group II to promote mandibular advancement. Anatomical changes in the condyle and mandible were evaluated by comparing radiographic results from before and after the study, with angular and linear measurements. Friedman and Mann-Whitney U-tests were used in statistical analysis. Results: According to the radiographic results, the growth of mandibles and condyles in Group II was significantly greater than with the length of the condylar process (A-B) and distance from condyle to menton (A-D) variables ( P < 0.05). In addition, Group I showed greater mandibular base growth than did Group II ( P < 0.05). Conclusions: We conclude that the use of an intraoral bite-jumping appliance can stimulate condylar growth and increase sagittal mandibular advancement in growing rats.